Distinct Frontoparietal Networks Set the Stage for Later Perceptual Identification Priming and Episodic Recognition Memory - Wimber, Maria (J Neurosci, 2010)
Recent imaging evidence suggests that a network of brain regions including the medial temporal lobe, ventrolateral prefrontal cortex, and dorsal posterior parietal cortex supports the successful encoding of long-term memories. Other areas, like the ventral posterior parietal and dorsolateral prefrontal cortices, have been associated with encoding failure rather than success. In line with the transfer-appropriate processing view, we hypothesized that distinct neural networks predict successful encoding depending on whether the later memory test draws primarily on perceptual or conceptual memory representations. Following an encoding phase, memory was assessed in a combined incidental perceptual identification and intentional recognition memory test. We found that during encoding, activation in ventral posterior parietal and dorsolateral prefrontal cortex predicted successful perceptual identification priming, whereas activation in ventrolateral prefrontal and dorsal posterior parietal cortex predicted successful recognition memory. Extending recent theories of attention to memory, the results suggest that ventral parietal regions support stimulus-driven attention to perceptual item features, forming memories accessed by later perceptual memory tests, whereas dorsal parietal regions support attention to meaningful item features, forming memories accessed by later conceptual memory tests.